2016
DOI: 10.1002/joc.4809
|View full text |Cite
|
Sign up to set email alerts
|

From accelerated warming to warming hiatus in China

Abstract: As the recent global warming hiatus has attracted worldwide attention, we examined the robustness of the warming hiatus in China and the related dynamical mechanisms in this study. Based on the results confirmed by the multiple data and trend analysis methods, we found that the annual mean temperature in China had a cooling trend during the recent global warming hiatus period, which suggested a robust warming hiatus in China. The warming hiatus in China was dominated by the cooling trend in the cold season, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 71 publications
(138 reference statements)
0
44
0
Order By: Relevance
“…The slight negative changes in the first three deciles for both T max and T min during the ‘warming hiatus’ period reflect Xie et al . ()'s finding of a cooling trend in the cold season in mean air temperature that induced more frequent and more extreme cold‐weather events. We can interpret these patterns in terms of seasonal change, which supports the assertion by Cohen et al .…”
Section: Resultsmentioning
confidence: 99%
“…The slight negative changes in the first three deciles for both T max and T min during the ‘warming hiatus’ period reflect Xie et al . ()'s finding of a cooling trend in the cold season in mean air temperature that induced more frequent and more extreme cold‐weather events. We can interpret these patterns in terms of seasonal change, which supports the assertion by Cohen et al .…”
Section: Resultsmentioning
confidence: 99%
“…The EAWM has also been shown to have a close relationship to the Siberian high, which is mainly caused by the cold land temperatures during the winter [ Gong and Wang , ; Xie et al ., ]. In recent decades, the Siberian high has strengthened, leading to stronger cold surges from the Arctic and generating winter cooling over East Asian dryland regions [ Xie et al ., ; Huang et al ., ]. On a hemispheric scale, Wallace et al .…”
Section: Impacts Of Atmosphere‐ocean Interactionsmentioning
confidence: 98%
“…At a regional scale, the monsoon is associated with the land‐sea thermal contrast, e.g., variations in East Asian winter monsoon (EAWM) intensity affect wintertime temperature and precipitation over Asian dryland regions. The EAWM has also been shown to have a close relationship to the Siberian high, which is mainly caused by the cold land temperatures during the winter [ Gong and Wang , ; Xie et al ., ]. In recent decades, the Siberian high has strengthened, leading to stronger cold surges from the Arctic and generating winter cooling over East Asian dryland regions [ Xie et al ., ; Huang et al ., ].…”
Section: Impacts Of Atmosphere‐ocean Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…() analysed meteorological records in China for the period of 1961–2004 and showed that the warming trend started around 1980 in most stations and that this phenomenon gradually occurred later from north to south. Nevertheless, through applying the period of global warming “hiatus” for a priori justification to regional scales (Chen and Zhai, ), several recent studies pointed out that China also experienced a warming “hiatus” since 1998 (Li et al ., ; ; Xie et al ., ; Shen et al ., ). In different regions, a strong warming “hiatus” in eastern China was observed during 1998–2013 (Chen and Zhai, ), especially in Northeast China (Sun et al ., ), whereas an accelerated warming trend was detected on the Tibetan Plateau over the same period (Duan and Xiao, ; Ma et al ., ).…”
Section: Introductionmentioning
confidence: 99%